SISTEM PAKAR PENANGANAN KERUSAKAN KOMPUTER DAN PERIPHERALNYA - Gufron Gufron; Danang Danang (Elkom : Jurnal Elektronika dan Komputer, 2018)
In operating a computer, of course, often experience problems with the Windows operating system, such as a slow computer when reading data, missing icons on the desktop, application system crashes or files that can not be run, or error messages appear that are not understood, problems that arise this is not uncommon fatal so that it interferes with the work or activity that is being done. One of the right solutions to the above problem is by applying an object-oriented design that follows the Hierarchy rules (tree rules), which is that each stage will bring up several new stages and Forward Reasoning inference techniques with Dept First Search data search techniques, with the forward reasoning system the system will provide information for the problems encountered. The test results show the solution to the problem of any computer damage problem can help computer users to recognize and deal with computer damage.